A The Analysis Of Performance Solar Panel Placement on the Deck House Fishing Vessel (30 GT) on Fishing Operation - Shanty Manullang; Rizky Irvana; Immanuel Thenu; John Karuwal (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
The integration of renewable energy systems in fishing vessels has increasingly attracted attention as an alternative approach to improving operational sustainability and reducing dependency on conventional energy sources. However, additional equipment installed above the deckhouse may influence vessel stability and operational performance. This study aims to investigate the effect of solar panel installation on the deckhouse of a 30 GT fishing vessel in terms of stability characteristics and fishing operational capability. The analysis was conducted using secondary vessel data and numerical simulations through Maxsurf software. Stability performance was evaluated using the A.N. Krylov method with verification based on International Maritime Organization intact stability criteria, while seakeeping performance was assessed using strip theory combined with the Joint North Sea Wave Project wave spectrum under various loading and wave conditions. The results indicate that solar panel installation slightly changes the vessel’s weight distribution but does not significantly affect stability performance, as all loading conditions satisfy the required stability criteria. Seakeeping analysis further shows that vessel performance is strongly affected by wave conditions, with the most favorable operational performance achieved at wave heights below 2 m. These findings demonstrate that solar panel integration can be implemented on fishing vessel deckhouses without significantly compromising vessel safety and operational performance under appropriate environmental conditions.